2019
DOI: 10.1111/cdev.13315
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Stimulation as a Mechanism Linking Socioeconomic Status With Executive Function: A Longitudinal Investigation

Abstract: Executive functions (EF), including working memory, inhibition, and cognitive flexibility, vary as a function of socioeconomic status (SES), with children from economically disadvantaged backgrounds having poorer performance than their higher SES peers. Using observational methods, we investigated cognitive stimulation in the home as a mechanism linking SES with EF. In a sample of 101 children aged 60–75 months, cognitive stimulation fully mediated SES‐related differences in EF. Critically, cognitive stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(155 citation statements)
references
References 57 publications
11
121
1
2
Order By: Relevance
“…This finding has been replicated in numerous studies (e.g. Hackman et al, 2015; Hackman et al, 2009; Rosen et al, 2018; Rosen et al, In Press). These findings demonstrate that SES is associated with differences in cognitive stimulation and environmental complexity including access to learning materials, parental involvement in learning, and even visual complexity of the home.…”
Section: Socio-economic Status and Cognitive Stimulationsupporting
confidence: 61%
See 2 more Smart Citations
“…This finding has been replicated in numerous studies (e.g. Hackman et al, 2015; Hackman et al, 2009; Rosen et al, 2018; Rosen et al, In Press). These findings demonstrate that SES is associated with differences in cognitive stimulation and environmental complexity including access to learning materials, parental involvement in learning, and even visual complexity of the home.…”
Section: Socio-economic Status and Cognitive Stimulationsupporting
confidence: 61%
“…In contrast to other proposed mechanistic explanations, cognitive stimulation accounts for the association between SES and EF across the entire SES distribution and highlights specific types of experiences that are likely to scaffold development of the PFC. Cognitive stimulation and the complexity of early linguistic experience have been associated with the development of EF and PFC structure and function in multiple studies (Hackman et al, 2010; Rosen et al, 2018; Sarsour et al, 2012; Sheridan et al, 2012; Rosen et al, In Press), and mediate the association of SES with EF and PFC structure, even after adjustment for exposure to stress or violence (Hackman et al, 2015; Rosen et al, 2018; Rosen et al, In Press). Differences in cognitive stimulation may contribute to EF disparities among children exposed to adversity, given the well-established reductions in cognitive stimulation observed among children exposed to caregiver deprivation and from low-SES households (Bradley and Corwyn, 2002; Bradley et al, 2001; Hart and Risley, 1995; Kantor et al, 2004; Smyke et al, 2007).…”
Section: Existing Models Of Environmental Experience and Ef Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In other countries, for example, in Arab Countries, bilinguals usually belong to a high social class and often learn more than one language because they receive a bilingual school education (Abdelgafar and Moawad, 2015 ). It is known that low socioeconomic status leads to lower cognitive functioning (Rosen et al, 2019 ). Given the high frequency of low socioeconomic status and reduced vocabulary in bilinguals, several authors have indicated the importance of analyzing these aspects and monitoring the effect of these variables statistically if a difference between groups is present.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research points towards extensive reorganisation occurring within the prefrontal cortex in early infancy [60]. Factors occurring within the first few months of life (Figure 1), such as parent-child interactions [61], including scaffolding [20] and interaction contingency [62], or levels of cognitive stimulation [63], may critically impact early brain development and the development of capacities such as attentional regulation, which form the 'building blocks' of EFs, later leading to altered EF development. Without such input in infancy, as may be the case in institutions, EF development may be perturbed.…”
Section: Cognitive Deprivationmentioning
confidence: 99%